Análise qualitativa de corpus documental (Cadernos de Linguagem e Sociedade, 2010)
This paper aims at discussing some qualitative procedures in a documental corpus. We took as basic support some concepts from the theoretical framework of French Discourse Analysis. Thus, such documents are treated like indexes of determination in the analysis. To illustrate our qualitative analysis, we chose a subject syllabus among the set of subjects offered in the Letters Course in a federal university in Brazil.